The form of forms. The project of architecture between necessity and possibility - De Regibus, Carlo; Giustiniano, Alberto (Scenari, 2021)
Nowadays, design theories often understate the relevance of aesthetic, as it could be reduced to a stylistic feature. Conversely, the paper investigates the aesthetic nature of architecture: both by inquiring into its ontological heteronomy from the point of view of design, and by looking at the work of art according to the theory of systems. Thus, the paper defines a theory of design which is a theory of architecture too, as it elevates the aesthetic to a most prominent role – consistent with its historical relevance, indeed: that is, to be the genuine criteria for evaluating the formative success of the project. For such a goal, both an architectural glance, to relate this perspective to actual design, and a philosophical one, to understand premises and consequence of such hypothesis, are mandatory. That’s why the paper proposes a side-by-side reading: on the one hand, an architectural thought about aesthetic, on the other, a philosophical one. The reader will have the chance, and the power, to build bridges between the two parts, so that the punctual inspiration of one part could serve also for the other: and in the belief that in those thresholds, theory may be changed in practices.